Potassium channels in cancer: from hallmarks to therapeutic targeting - Yi-ling Zhang; Rong-jia Shi; Xin-hua Liang (Journal of Physiology and Biochemistry, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Addressing fruit allergen detection gaps: A validated LC-MS/MS method for eight allergenic fruits in foods - Yingnan Shencheng; Meizhen Zhou; Yumeng Zhao; Siyi Li; Yutong Xu; Yanan Gao; Xiaoxue Jia; Min Gao; Rong Zhang; Shuyan Liu; Feng Ye; Ya Zhang; et al. (Food Chemistry, 2026)

Mechanical behaviour, deformation mechanisms and support optimization of tunnels in gentle dip layered rock after freeze–thaw cycles - Xiao-Hu Zhang; Jia-Bing Zhang; Jun-Bin Fu; Rong-Huan Du; Han-Lin Wang (Tunnelling and Underground Space Technology, 2026)

Algicidal characteristics and mechanism of a newly identified bacterium Pseudomonas fulva EH5 against Microcystis aeruginosa - Rong Xiang; Tongpeng Jia; Geqi Zhang; Xue Sun; Nianjun Xu; Binghui Zheng (Journal of Hazardous Materials, 2026)

Sinocrassula zhaotongensis (Crassulaceae), a New Species From China - Ling‐Nan Wei; Jing Zhao; Jian‐Rong Zhang; Zi‐Xian Liu; Jia‐Guan Wang (New Zealand Journal of Botany, 2026)
Sinocrassula zhaotongensis , a new species of Crassulaceae from Yunnan Province, China, is described and illustrated. Morphologically, S. zhaotongensis is characterized by a glabrous plant surface, asymmetrically triangular to lanceolate basal leaves, triangular‐lanceolate sepals, and triangular petals that are yellowish at the base with dense purple‐red stripes and spots on the surfaces upward. Phylogenetic analyses based on concatenated chloroplast and nuclear DNA sequences strongly support S. zhaotongensis as a distinct lineage and sister to S. adpressa .

Environmental eustress inhibits CCL2 to overcome doxorubicin-induced cardiotoxicity and alleviate tumor growth - Peiyuan Bai; Chaobao Liu; Ao Liu; Zehao Zhuang; Jinghong Zhang; Lu Tang; Naifu Wan; Runda Wu; Wuwei Rong; Siqin Chen; Jinglei Wan; Yang Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Impact of fulvic acid on copper exposure in Ulva prolifera: Integrative insights from growth, physiology, transcriptomics, and physico-chemical characteristics - Tongpeng Jia; Geqi Zhang; Yahe Li; Xinchuan Yang; Nianjun Xu; Rong Xiang (Journal of Hazardous Materials, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Biochar–bentonite composite enabling antibiotic removal and greenhouse gas mitigation in waters - Yan Sun; Xiang Jia; Le Dai; Wei Ding; Yongjie Wang; Jin Zhang; Huan He; Nan Rong; Pei Lei (Chemical Engineering Journal, 2026)

Granite weathering revealed by magnesium isotopes fractionation: Implications for the flux dynamics and global carbon sink - Kai Luo; Jin-Long Ma; Fang-Zhen Teng; Gang-Jian Wei; Guan-Hong Zhu; Jia-Rong Liu; Zhuo-Ying Zhang; Zhi-Bing Wang (Chemical Geology, 2026)

Differential Enrichment of Deep Shale Gas in Southeastern Sichuan Basin: Dynamic Evolution and Preservation Mechanisms - Ke Zhang; Haikuan Nie; Songhang Zhang; Tianwu Xu; Zhujiang Liu; Chuanxiang Sun; Chengxiang Wan; Wei Dang; Pei Li; Jia Rong; Shuheng Tang (Journal of Earth Science, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Sodium alginate bead flotation assisted by cationic cellulose nanofibers for polystyrene microplastic removal - Linjuan Zhang; Hao Wen; Kemin Wei; Xichen Zheng; Jia He; Manli Wang; Peng Wei; Shaoli Fan; Guiwen Rong (Process Safety and Environmental Protection, 2026)

Antioxidant peptides from porcine blood meal: Mechanisms of interaction with hemin via spectroscopy and molecular docking - Rong Jia; Juanjuan Du; Jinxuan Cao; Jinpeng Wang; Yuemei Zhang; Wendi Teng; Ying Wang (Food Chemistry, 2026)

A 1D stepped coordination polymer based on Cu4I4 units for X-ray imaging over a broad temperature range - Ji-Hui Jia; Xiang-Long Hu; Dong Liang; Qianting Wang; Rong Zhang; Can-Zhong Lu (Chemical Engineering Journal, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Mapping coastal aquaculture ponds in China without dependence on water levels: New insights from pond dikes derived from Sentinel-1/2 imagery - Chuanpeng Zhao; Mingming Jia; Rong Zhang; Quan Han; Chunying Ren; Zongming Wang (Environmental Impact Assessment Review, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

Methionine-driven covalent chelation of Zn2+ by linusorb: a paradigm in hydrophobic cyclic peptide metal binding - Yi-kang Zhang; Du-jian Deng; Zhong-yi Luo; Wan-nan Wang; Jun-le Li; Shao-rong Zhang; Jia-li Li; Jia-zi Chen; Yong Wang; Zi-zhe Cai (Food Chemistry, 2026)

Enzyme-triggered polyelectrolyte complex for broad-spectrum antifungal therapy and biofilm eradication - Chuming Pang; Yimin Wang; Hui Zhang; Xuan Zhou; Siga Jia; Shize Leng; Rong Liu; Liangzhi Hong (Chemical Engineering Journal, 2026)

Magnetic biochar combined with digestate bioaugmentation synergistically accelerates the recovery of a collapsed anaerobic digestion system - Bao-Shan Xing; Yong-Ning Feng; Jia-Yi Liu; Yi Zhang; Guangyin Zhen; Samir Ibrahim Gadow; Rong Chen; Xiaochang C. Wang; Yu-You Li (Chemical Engineering Journal, 2026)

Metabolic reprogramming by baicalein disrupts fibroblast–macrophage crosstalk in idiopathic pulmonary fibrosis - Wen Zhang; Liu-Liu Yuan; Jia-Rong Li; Tian-Sheng Zheng; Li-Hong Fan (Chemico-Biological Interactions, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

The ATG14: multi-layer autophagy control and an emerging therapeutic target in cancer - Wenbo Wang; Chujuan Yu; Fulin Sun; Ruofeng Wang; Weikai Xia; Qinghang Song; Huhu Zhang; Zhenzhen Jia; Min Zhang; Haoran Wang; Zhenxiang Wang; Rong Fu; et al. (Apoptosis, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

Global patterns and soil controls governing terrestrial nitrogen cycling in response to experimental warming: A meta-analysis - Sen-Mao Zhang; Wan-Jia Hu; Xin-Rong Shi; Robert L. Kallenbach; Zhi-You Yuan (Soil Biology and Biochemistry, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Waste eggshell derived porous skeleton with dual functional CNT synergistically enhance the thermal property of PCMs for thermal management - Pei Li; Yuwei Fan; Xuyan Song; Yiyi Wang; Weijian Liu; Jia Liu; Han Sun; Xin-Rong Zhang (Bioresource Technology, 2026)

Superenhancer-driven SMC4 promotes myeloma growth by epigenetically enhancing IFI16-dependent STING signaling - Jiayun Guan; Xuanyi Lin; Zhenfeng Dai; Jianbiao Zhou; Zhen Cai; Tze King Tan; Tae-Hoon Chung; Xiaochen Zhang; Wee-Joo Chng; Xiaoxiang Rong; Yunlu Jia (Apoptosis, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Identification of a novel selenium peptide from Oryzain α hydrolysate: Selenium-specific database establishment, sequence confirmation, and molecular interaction analysis - Xin Wang; Bailiang Xue; Rong Zhang; Lin Shi; Wei Jia (Food Bioscience, 2026)

From origin tracing, processing, to quality regulation: Molecular mechanism advances in medicinal foods research by integrating multi-omics tools - Jian-Hang Cai; Guan-Dong Fang; Yan Zhang; Jie Song; Jia-Yi Weng; Xue-Mei Ge; Issoufou Amadou; Xiang-Rong Cheng (Food Bioscience, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

Cover cropping shifts microbial life-history strategies to promote necromass carbon accumulation through soil metabolite mediation in orchard systems - Yutao Zhang; Jia Liu; Kailou Liu; Daming Li; Rong Cui; Yaxin Liu; Xingjia Xiang; Ming Liu (Soil and Tillage Research, 2025)

Screening, synthesis and anti-fatigue function verification of selenopeptides - Lin Shi; Wei Jia; Rong Zhang; Haizhen Mo (Food Research International, 2025)

Adulteration of animal-derived whey protein in infant formula: High-throughput screening of characteristic peptides - Lin Shi; Wei Jia; Rong Zhang; Xin Wang; Haizhen Mo (Food Research International, 2025)

An injectable and programmable hydrogen delivery system for modulation tendon tissue in tendon-bone interface microenvironment - Tao Yuan; Fei Jin; Lili Qian; Xiaojiang Yang; Xin Yu; Zhongyang Lv; Ziying Sun; Shiwen Shen; Hong Qian; Jia Meng; Hui Jiang; Wenshuang Sun; et al. (Chemical Engineering Journal, 2025)

Carbon emissions from desert soil regulated by non-rainfall water inputs and their potential mechanisms - Xing Guo; Fan Du; Jungang Yang; Shihang Zhang; Kai Shi; Yongxing Lu; Xiaoying Rong; Jun Zhang; Rongliang Jia; Lu Gong; Yuanming Zhang; Xiaobing Zhou (CATENA, 2025)

Effects of Optimized Nitrogen Fertilizer Application on Chlorophyll Fluorescence Characteristics and Dry Matter Accumulation in Sugar Beet - Shi-Feng Dong; Lei Wei; Xing-Bo Tong; Yi-Na Zhang; Rong-Li Jia; Xu-Ming Xing; Shu-De Shi (Sugar Tech, 2025)

Trichoderma azadirachtae Ta3302: A novel biocontrol agent for banana Fusarium wilt and a promoter of plant growth - Mei Luo; Qiu-Rong Huang; Meng-Xuan Jia; Jin-Ying Zeng; En-Ru Dong; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2025)

Δ-Decanolactone targets PLIN2 and FABP3 in goat milk: Longitudinal multi-omics framework unravels structural destabilization and metabolic reprogramming from flavor fraud - Rong Zhang; Wei Jia (Food Research International, 2025)

Deep learning-derived optimal annotation strategies to power the systematic mapping of peptide space - Lele Yue; Wei Jia; Rong Zhang (Food Chemistry, 2025)

Novel insights to the synergistic effects of magnetic biochar in anaerobic digestion while treating synthetic organic wastewater for biomethane recovery - Zhang-Wei He; Yuan-Long Jia; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Aijie Wang; Rong Chen (Chemical Engineering Journal, 2025)

Conformation-driven fluorocarbon-powered zinc(II) phthalocyanine for photodynamic therapy in hypoxic tumors via anti-aggregation, oxygen retention, and enhanced cellular uptake - Di Gao; Liangliang Jia; Xinyuan Zhang; Rong Yun; Xinyang Liu; Bin Qin; Zhongmin Tian; Zhe Yang (Chemical Engineering Journal, 2025)

Bicarbonate ions enhanced surface Fe(II) regeneration and peroxymonosulfate activation on stainless-steel scrubber cathode for BPA degradation - Danni Deng; Rong Chen; Qianqian Zhong; Binbin Xiong; Jia Deng; Na Zhang; Shiwei Xie (Journal of Water Process Engineering, 2025)

CTAB-Assisted, controlled preparation of a CeZrOx/CuSAPO-34 catalyst and its performance for the synergistic removal of NOx and toluene from flue gas - Qian Zhou; Xuehui Jia; Rong Liu; Fangfei Liu; Han Zhang; Dan Hou; Lu Wang; Yunkuo Luo; Bichun Huang; Hong Huang; Xia Gong; Chenglong Yu (Journal of Environmental Chemical Engineering, 2025)

Estimating daily NOx and CO2 emissions in typical megacities of east China using TROPOMI NO2 observations - Yizhen Jia; Minghui Tao; Hongming Zhang; Pengfei Ma; Bin Zhao; Rong Li; Dejia Yin; Lijuan Zhang; Haijun Huang; Lunche Wang; Yi Wang; Liangfu Chen (Atmospheric Environment, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Complete genome of Thalassotalea piscium NK451B, an Antarctic bacterium with abundant extracellular proteases - Jia-Yi Song; Zi-Ying Li; Xiao-Hui Yang; Jin-Rong Wei; Kang Li; Yi Zhang (Marine Genomics, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Implementation and topological characterization of Weyl exceptional rings in quantum-mechanical systems - Hao-Long Zhang; Pei-Rong Han; Xue-Jia Yu; Shou-Bang Yang; Jia-Hao Lü; Wen Ning; Fan Wu; Qi-Ping Su; Chui-Ping Yang; Zhen-Biao Yang; Shi-Biao Zheng (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

Accelerating enrichment of ARGs and MGEs with increasing ammonium removal during partial nitrification treating high-strength ammonia wastewater - Heng Yu; Weiyi Jia; Yuqiu Luo; Rong Zhang; Junkai Zhao; Cong Lu; Yue Dong; Shuo han; Bing Li; Chengtun Qu (Environmental Research, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Machine learning-based design, screening, and activity validation of topoisomerase I inhibitors - Ya-Kun Zhang; Jian-Bo Tong; Jia-Le Li; Rong Wang; Yan-Rong Zeng (Molecular Diversity, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Synergistic estimation of mangrove canopy height across coastal China: Integrating SDGSAT-1 multispectral data with Sentinel-1/2 time-series imagery - Mingming Jia; Rong Zhang; Chuanpeng Zhao; Yaming Zhou; Chunying Ren; Dehua Mao; Huiying Li; Genyun Sun; Hongsheng Zhang; Wensen Yu; Zongming Wang; Yeqiao Wang (Remote Sensing of Environment, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Identification and validation of mitochondrial endoplasmic reticulum membrane-related genes in atherosclerosis - Li-Rong Wang; Chun-Xi Zhang; Lv-Bo Tian; Jie Huang; Li-Jun Jia; Hao Tao; Neng-Wei Yu; Bing-Hu Li (Mammalian Genome, 2025)

Addressing accuracy challenges in machine learning for debris flow susceptibility: Insights from the Yalong River basin - Zaiyang Ming; Jianqiang Zhang; Haiqing He; Lili Zhang; Rong Chen; Yang Jia (Journal of Mountain Science, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

The promotional effect of MoO3 on the CeO2/TiO2 catalyst for simultaneous removal of NO and toluene: From the insights of experimental and DFT studies - Zhuang Hu; Yi-fei Yu; Hai-yuan Zhao; Zheng-long Wu; Rong Guo; Jia-le Zhou; Xin-yue Zhou; Bing Zhang; Yang-wen Wu; Li Zhao; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

A multi-perspective understanding of population change in migratory species: A case study with pied avocets (Recurvirostra avosetta) in East Asia - Yang Wu; Weipan Lei; Entao Wu; Han Pan; Yifei Jia; Cai Lu; Yongxiang Han; Junjie Wang; Rong Fan; Zhijun Ma; Zhengwang Zhang; Richard A. Fuller (Biological Conservation, 2025)

A Global Synthesis of How Plants Respond to Climate Warming From Traits to Fitness - Pengyan Jia; Rong Zhang; Bernhard Schmid; Han Wang; Jin‐Sheng He; Jiaxi Liu; Sijie Liu; Sipeng Jian; Yanhao Feng (Ecology Letters, 2025)
Despite intensive research, our understanding of how plants respond to warming by coordinating their full arsenal of traits to adjust fitness is lacking. To fill this gap, we applied a trait‐based framework with three clusters (two functional clusters: “carbon‐fixation rate” and “carbon‐fixation area”; a third cluster: “total carbon fixation”) to a global dataset compiled from 572 studies of warming experiments with 677 species and a comprehensive list of traits and fitness components. The pairwise correlation analysis complemented with SEM and PCA showed that plants increased biomass (the core variable in the third cluster) under warming by coordinating satellite traits in two functional clusters to adjust their core traits, net photosynthesis rate and total leaf area, respectively. In particular, the trait coordination was characterised by the maintenance of net photosynthesis rate and the increase of total leaf area, which was robust across ecological contexts although warming responses of the variables per se displayed context‐dependences. Moreover, the trade‐offs between biomass and reproduction (itself bearing mass vs. number trade‐offs) in their warming responses scaled the coordination to enhance fitness except in the contexts where reproduction was reduced. These findings could help explain and predict plant form and function in a warming world.

Integrative deep learning framework predicts lipidomics-based investigation of preservatives on meat nutritional biomarkers and metabolic pathways - Wei Jia; Aiai Guo; Wenwen Bian; Rong Zhang; Xin Wang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Quantitative characterization of global nighttime light: A method for measuring energy intensity based on radiant flux and SNPP-VIIRS data - Haihang Zeng; Mingming Jia; Xiangyu Ning; Zhaohui Xue; Rong Zhang; Chuanpeng Zhao; Yangyang Yan; Zongming Wang (Remote Sensing of Environment, 2025)

Extraction of short-chain fatty acid ethyl Ester in Baijiu using covalent organic framework–based magnetic nanoparticles: Theoretical screening and experimental validation - Xiaolong Shang; Ying Han; Xudong Lian; Siting Ye; Ling Ao; Baoguo Sun; Rong Liu; Pan Zhen; Yongqing Zhang; Yintao Jia; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The influence of carbon dioxide on fermentation products, microbial community, and functional gene in food waste fermentation with uncontrol pH - Xin-Rong Pan; Pei-Ken Shang-Guan; Shu-Hui Li; Chu-Hao Zhang; Jia-Min Lou; Liang Guo; Lu Liu; Yin Lu (Environmental Research, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Characterization of Gut Microbiota in Rats and Rhesus Monkeys After Methamphetamine Self-administration - Li He; Jia-hui Zhou; Huan Li; Wen-lei Zhang; Tie-qiao Liu; Hai-feng Jiang; Rong-wei Zhai; Xiao-jie Zhang (Molecular Neurobiology, 2025)

Amelioration impact of gut-brain communication on obesity control by regulating gut microbiota composition through the ingestion of animal-plant-derived peptides and dietary fiber: can food reward effect as a hidden regulator? - Wei Jia; Jian Peng; Yan Zhang; Jiying Zhu; Xin Qiang; Rong Zhang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2024)

Effects of changing spatial scale on debris-flow hazard assessment: A case study in the Dadu River basin, China - Lili Zhang; Jianqiang Zhang; Zaiyang Ming; Haoyu Li; Rong Chen; Yang Jia (Science of The Total Environment, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Recycle of residual ammonium from weathered crust elution-deposited rare earth tailings via an efficient combined method of elution, struvite precipitation and on-line adsorption - Kejia Wu; Junxia Yu; Jia Wang; Xiaodi Li; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Journal of Water Process Engineering, 2024)

Quantitative mechanisms for the Cd2+ adsorption increased by sewage-sludge biochar but decreased by rice-straw biochar after melamine modification - Zi-Xuan Yin; Yun-Yi Zhang; Jia-Xin Liu; Fei Huang; Qian-Jun Liu; Ming-Zhi Huang; Rong-Bo Xiao; Guo-Yi Gao; Tian-Zhen Lan; Xiao Zhou (Journal of Environmental Chemical Engineering, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Advancing mangrove species mapping: An innovative approach using Google Earth images and a U-shaped network for individual-level Sonneratia apetala detection - Chuanpeng Zhao; Yubin Li; Mingming Jia; Chengbin Wu; Rong Zhang; Chunying Ren; Zongming Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Data mining-based identification of epigenetic signatures with discrimination potential of lung adenocarcinoma and squamous cell carcinoma - Wen-guang Pang; Min Ye; Jia-rong Chen; Liang Zhang; Zheng Wang (Molecular Biology Reports, 2024)

Transfer from ciliate to zebrafish: Unveiling mechanisms and combined effects of microplastics and heavy metals - Yan Zhang; Caixia Wang; Ruiqi Jia; Hongan Long; Jianfeng Zhou; Gaojingwen Sun; YunLong Wang; Zhaoji Zhang; Xiaozhi Rong; Yong Jiang (Journal of Hazardous Materials, 2024)

Novel photic responsive Janus nanoparticles: Interfacial catalysts for efficient preparation of biodiesel - Mingshu Li; Rong Zhang; Chuanxing Jia; Zhongqiu Liu; Yujing Liu; Anguo Ying (Fuel, 2024)

Improving curcumin bioavailability: Targeted delivery of curcumin and loading systems in intestinal inflammation - Junyi Zhao; Wei Jia; Rong Zhang; Xin Wang; Li Zhang (Food Research International, 2024)

Robust polymer electrolytes with fast ion-transport nanochannels constructed by carbon dots for long lifespan Li metal batteries - Jia-Wen Ni; Xi-Rong Zhang; Tian-Bing Song; Zun-Hui Huang; Qian-Li Ma; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

Lithium-ion battery future degradation trajectory early description amid data-driven end-of-life point and knee point co-prediction - Ganglin Cao; Yao Jia; Shouxuan Chen; Yuanfei Geng; Shuzhi Zhang; Haibin Lu; Rong Feng; Ning Wang; Xiongwen Zhang (Journal of Cleaner Production, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Assessment of the hormesis effect and toxic damage of short-term low-dose aflatoxin B1 in grass carp (Ctenopharyngodon idellus) - Jin-long Li; Jia-rong Guo; Pei Wang; Jun-zhi Zhang; Zhi-gang He; Jin-long Wang; Yi Hu (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the hormesis and toxicity of short-term low-dose aflatoxin B1 in grass carp ( Ctenopharyngodon idellus ). Triplicate isonitrogenous and isocaloric aflatoxin B1 diets—CD (control, 0 ug/kg), D1 (20 ug/kg), and D2 (500 ug/kg)—were prepared and fed to grass carp with an initial mean body weight of (15.2 ± 0.1) g for 56 days. The results showed that the weight gain rate and specific growth rate of grass carp fed diet D2 were significantly higher, and the feed coefficient and crude fat content of the whole body were significantly lower ( P < 0.05) compared with those fed diet CD. Serum superoxide dismutase content of grass carp fed D1 diet increased significantly ( P < 0.05) with an increasing dose of aflatoxin B1, but when the dose reached 500 ug/kg (D2), serum superoxide dismutase, complement C3, and immunoglobulin M of grass carp decreased significantly ( P < 0.05), while malondialdehyde increased significantly ( P < 0.05). After short-term feeding of aflatoxin B1-containing diets (D1 and D2), liver body index, visceral body index, serum total cholesterol, triglyceride, and urea nitrogen content of grass carp increased significantly ( P < 0.05), total bile acid secretion decreased significantly ( P < 0.05), and structural damages such as increase in vacuoles, organizational structure loosening, and nucleus translocation were observed in the liver. Meanwhile, liver function indexes such as serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase increased significantly with the increase of aflatoxin B1 dose ( P < 0.05). In addition, the height of intestinal villi, crypt depth, villus–crypt ratio, and tubular cell number, as well as the content of trypsin and lipase activities in the intestine of grass carp in the D2 group, were significantly higher than those in the CD group ( P < 0.05). In conclusion, after a short-term intake of low doses of aflatoxin B1 (≤500 ug/kg), the toxicological damage of aflatoxin B1 was pronounced, although it produced a certain degree of hormesis on the growth performance and intestinal structure and function of grass carp. At a dose of 20 ug/kg, the non-specific immune system and liver structure and function of grass carp showed obvious toxic damage.

Dietary anthocyanins as natural phytochemicals for regulating hyperuricemia: Proposed intestinal flora, key enzyme activity, and anti-inflammatory pathways - Shuai Lv; Wei Jia; Rong Zhang; Li Zhang (Trends in Food Science & Technology, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Effects of polyphenols from walnut pellicle on the structure and allergenicity of walnut globulin - Jia-Hui Ma; Li-Qiu Ren; Tian-Xuan Tang; Yu-Yao Chen; Chen-Xi Zhang; Yu-Feng Ke; Yan Zhang; Mitchell N. Muskat; Xiang-Rong Cheng (Food Bioscience, 2024)

Empagliflozin attenuates doxorubicin-impaired cardiac contractility by suppressing reactive oxygen species in isolated myocytes - Rong Lin; Xiaodong Peng; Yukun Li; Xuesi Wang; Xinmeng Liu; Xingze Jia; Chengjun Zhang; Nian Liu; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

NCOA4-mediated ferritinophagy participates in cadmium-triggered ferroptosis in spermatogonia - Didi Jia; Mingming Zhang; Mengyuan Li; Wenjing Gong; Wei Huang; Rong Wang; Yihang Chen; Qizi Yin; Jie Wu; Zhongxiu Jin; Juan Wang; Yehao Liu; et al. (Toxicology, 2024)

Intestinal microbiota via NLRP3 inflammasome dependent neuronal pyroptosis mediates anxiety-like behaviour in mice exposed to 3.5 GHz radiofrequency radiation - Gui-qiang Zhou; Xing Wang; Peng Gao; Tong-zhou Qin; Ling Guo; Zhao-wen Zhang; Zhi-fei Huang; Jia-jin Lin; Yun-tao Jing; Hao-nan Wang; Chun-ping Wang; Gui-rong Ding (Science of The Total Environment, 2024)

Mangrove species mapping in coastal China using synthesized Sentinel-2 high-separability images - Chuanpeng Zhao; Mingming Jia; Rong Zhang; Zongming Wang; Chunying Ren; Dehua Mao; Yeqiao Wang (Remote Sensing of Environment, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Effects of arsenic on the transport and attachment of microplastics in porous media - Jia Guo; Haifeng Rong; Lei He; Cuibai Chen; Baogang Zhang; Meiping Tong (Journal of Hazardous Materials, 2024)

High-throughput analysis of hazards in novel food based on the density functional theory and multimodal deep learning - Lin Shi; Wei Jia; Rong Zhang; Zibian Fan; Wenwen Bian; Haizhen Mo (Food Chemistry, 2024)

Chemical constituents and chemotaxonomic research of the deep-sea-derived fungus Aspergillus japonicus W6 - Tong Yu; Rong Chao; Zheng-Biao Zou; Jia-Xin Duan; Kai Zhang; You Li; Ming-Min Xie; Yong Zhang; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Nighttime light in China's coastal zone: The type classification approach using SDGSAT-1 Glimmer Imager - Mingming Jia; Haihang Zeng; Zuoqi Chen; Zongming Wang; Chunying Ren; Dehua Mao; Chuanpeng Zhao; Rong Zhang; Yeqiao Wang (Remote Sensing of Environment, 2024)

Massive early Middle Pleistocene cheetah from eastern Asia shed light onto the evolution of Acinonyx in Eurasia - Qigao Jiangzuo; Yaming Wang; Joan Madurell-Malapeira; Saverio Bartolini Lucenti; Shijie Li; Shiqi Wang; Zhaoyu Li; Rong Yang; Yi Jia; Lu Zhang; Shanqin Chen; Changzhu Jin; et al. (Quaternary Science Reviews, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Ent-atisane diterpenoids from Euphorbia wallichii and their anti-influenza A virus activity - Jie Zhang; Xiao-Jia Guo; Xiao-Juan Chen; Rong-Rong Zhang; Bai-Ping Ma; Zhong-Qiu Liu (Phytochemistry, 2024)

Prediction of surface settlement around subway foundation pits based on spatiotemporal characteristics and deep learning models - Wen-Song Zhang; Ying Yuan; Meng Long; Rong-Han Yao; Lei Jia; Min Liu (Computers and Geotechnics, 2024)

Artificial infection pathway of largemouth bass LMBV and identification of resistant and susceptible individuals - Ya Zhang; Bin Gui; Zhihui Jia; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

The effect of lactic acid bacteria fermentation on physicochemical properties of starch from fermented proso millet flour - Tongze Zhang; Siqi Hong; Jia-Rong Zhang; Pin-He Liu; Siyi Li; Zixian Wen; Jianwei Xiao; Guirong Zhang; Olivier Habimana; Nagendra P. Shah; Zhongquan Sui; Harold Corke (Food Chemistry, 2024)

Photo-driven dynamic hydrogel modulates bone marrow mesenchymal stem cells behavior for enhanced cartilage regeneration - Wenjie Zhang; Wenliang Xue; Zhaoli Jia; Rong Yang; Penghui Wang; Yi Hu; Xiaoyan Tan; Qiang Chen; Bo Chi (Chemical Engineering Journal, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Systematic investigation on the multi-scale mechanisms of bitter peptide self-assembly for flavor modulation - Rong Zhang; Wei Jia (Food Chemistry, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Adulteration of endogenous substances as a next challenge in dairy safety: High-throughput analysis of flavours in goat milk based on the molecular mechanism of flavouring components dynamic changes - Lin Shi; Wei Jia; Rong Zhang; Zibian Fan; Haizhen Mo (Trends in Food Science & Technology, 2023)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Exploring novel ANGICon-EIPs through ameliorated peptidomics techniques: Can deep learning strategies as a core breakthrough in peptide structure and function prediction? - Wei Jia; Jian Peng; Yan Zhang; Jiying Zhu; Xin Qiang; Rong Zhang; Lin Shi (Food Research International, 2023)

Effect of geographical origins and pile-fermentation on the multi-element profiles of ripen Pu-erh tea revealed by comprehensive elemental fingerprinting - Jiayi Zhu; Le Chen; Yue Chen; Yuting Rong; Yongwen Jiang; Fuqiao Liu; Qinghua Zhou; Xuehong Wei; Haibo Yuan; Junjie Zhang; Jia Li (Food Control, 2023)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Treg plasticity and human diseases - Zheng Zhang; Jihua Guo; Rong Jia (Inflammation Research, 2023)

First principles insights into the interaction mechanism of iron doped thermally activated kaolinite with Cd and Pb pollutants in organic solid waste incineration flue gas - Yang-wen Wu; Rong Guo; Li-juan Sun; Xin-yue Zhou; Jia-le Zhou; Hai-yuan Zhao; Yi-fei Yu; Zhuang Hu; Bin Hu; Ji Liu; Bing Zhang; Li Zhao; et al. (Waste Management, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Efficient capture of iodine by charge-induced effect of nitrogen-rich ionic liquids - Shi-Jie Guo; Guo-Hao Zhang; Qiu-Hong Zhu; Chao Yu; Jia-Ying Liu; Xiao-Lan Yang; Song Qin; Nan-Rong Zhao; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Adaptability law of central heating environment under the effect of thermal history: A continuous field survey - Chao Jia; Xihao Bie; Chang Sun; Zhicheng Zhang; Yonghua Rong; Jing Cao; Menghan Wang (Building and Environment, 2023)

Inactivation of airborne pathogenic microorganisms by plasma-activated nebulized mist - Li Guo; Pengyu Zhao; Yikang Jia; Zifeng Wang; Min Chen; Hao Zhang; Dingxin Liu; Yong Zhang; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2023)

The space-charge region at NiFe-MOF⊆LDH p-n junction by self-sacrificing LDH to boost oxygen evolution tandem with in-situ electro-Fenton - Na Zhang; Shi-Xian Guan; Qing Zhang; Jia-Rong Zhao; Jian-Yong Zhang; Qin-Fei Ke; Yong-Zheng Fang (Chemical Engineering Journal, 2023)

In vitro adventitious regeneration and plantlet transplantation of Atractylodes chinensis (DC.) Koidz., a valuable medicinal plant - Wenhao Jia; Junbo Rong; Mengyang Zhang; Wenyue Peng; Xutong He; Xiujuan Lei; Yingping Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Effects of nano-silicon dioxide on minerals, antioxidant enzymes, and growth in bitter gourd seedlings under cadmium stress - Hongyan Sun; Bo Zhang; Zhijiang Rong; Songjie He; Yifan Gao; Jia Yu; Qingmei Zhang (Acta Physiologiae Plantarum, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Zn anode surface engineering for stable zinc-ion batteries: Carbon dots incorporated mesoporous TiO2 as a coating layer - Tian-Bing Song; Qian-Li Ma; Xi-Rong Zhang; Jia-Wen Ni; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

One-step electrodeposition preparation of boron nitride and samarium co-modified Ti/PbO2 anode with ultra-long lifetime: highly efficient degradation of lincomycin wastewater - Maojie Zhao; Mengqi Yang; Peilin Yang; Rong Su; Feng Xiao; Ping He; Hongquan Deng; Tinghong Zhang; Bin Jia (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

One new elemane sesquiterpenoid glycoside and five glycoglycerolipids from Pittosporum truncatum with anti-bacterial activity - Rong Huang; Ji-Li Deng; Sheng-Nan Guan; Jia-Qi Ding; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Deciphering the competitive binding interaction of β-lactoglobulin with benzaldehyde and vanillic acid via high-spatial-resolution multi-spectroscopic - Rong Zhang; Wei Jia (Food Hydrocolloids, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Effects of dietary supplementation of Anabaena sp. PCC7120 expressing VP28 protein on survival and histopathology after WSSV infection in Macrobrachium nipponense - Yupei Tong; Jia Yang; Li Wang; Xiaoping Chi; Chan Zhu; Rong Yin; Le Zhang; Yaru Li; Chunyan Zhao; Rui Jia (Fish & Shellfish Immunology, 2023)

People's psychological and physiological responses to the combined smell-thermal environments - Chao Jia; Yonghua Rong; Xiaoying Geng; Menghan Wang; Zhicheng Zhang; Shengnan Han; Xihao Bie (Building and Environment, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Effect of flue gas components on the removal of cadmium pollutants by transition metal-modified activated carbon: Density functional theory and thermodynamic study - Xin-Yue Zhou; Jia-Le Zhou; Rong Guo; Yin-jie Liu; Yi-fei Yu; Bing Zhang; Yang-Wen Wu; Li Zhao; Qiang Lu (Fuel, 2023)

Amorphous biomineral-reinforced hydrogels with dramatically enhanced toughness for strain sensing - Jia-hua Liu; Zhengyi Mao; Yuhan Chen; Yunchen Long; Haikun Wu; Junda Shen; Rong Zhang; Oscar W.H. Yeung; Binbin Zhou; Chunyi Zhi; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2023)

PSMD4 drives progression of hepatocellular carcinoma via Akt/COX2 pathway and p53 inhibition - Jiamin Zhang; Shu Fang; Fanghao Rong; Miaomiao Jia; Yunpeng Wang; Huixian Cui; Peipei Hao (Human Cell, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Characterization of dissolved organic matter content, composition, and source during spring algal bloom in tributaries of the Three Gorges Reservoir - Rong Xiang; Zebin Tian; Chuandong Zhang; Binghui Zheng; Haifeng Jia (Science of The Total Environment, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

Four anti-inflammatory aromadendrane sesquiterpenoid fucosides and other constituents from Pittosporum glabratum var. neriifolium - Bai-Tong Sha; Rong Huang; Qiang-Guo Zhang; Sheng-Nan Guan; Jia-Qi Ding; Xin-Zheng Liu; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Monitoring the light pollution changes of China’s mangrove forests from 1992-2020 using nighttime light data - Haihang Zeng; Mingming Jia; Rong Zhang; Zongming Wang; Dehua Mao; Chunying Ren; Chuanpeng Zhao (Frontiers in Marine Science, 2023)
Mangrove forests are one of the most biologically diverse and productive ecosystems on Earth. They are important breeding and nursing grounds for amphibians, invertebrates, birds, fish, etc. Light pollution may cause serious degradation of biodiversity in the ecosystem. A report of the long-term holistic views of light pollution changes is essential for sustainable management of mangrove ecosystems. However, to date, such studies have rarely been carried out. This study aimed to monitor the long-term light pollution changes of China’s mangrove forests. To achieve this goal, we used time-series nighttime light (NTL) data to build continuous light pollution data. NTL maps made with DMSP-OLS (DNL) or NPP-VIIRS (VNL) are widely utilized in research on human activity. However, DMSP and VIIRS images are different in spatial resolution, radiation resolution, and data saturation. Thus, this study innovatively set an optimal threshold for generating consistent light pollution data in mangrove areas from 1992-2020. The results showed that: (1) the proportion of light-polluted mangrove forests in China increased from 12% in 1992 to 52% in 2020; (2) the largest net increase occurred in Guangxi with an area of 4,086 ha, followed by Guangdong (3,365 ha) and Hainan (2,944 ha); (3) Zhejiang had the largest proportion of net growth (from 0% in 1992 to 99% in 2020), followed by Hainan (66%) and Fujian (59%). Mangrove forests have been protected and restored for decades in China; this study indicates that the establishment of nature reserves is effective in preventing the light pollution of mangroves and provides the first long-term multi-temporal dataset of light pollution in China’s mangrove forests. This comprehensive information could support related studies and facilitate the development of applicable coastal management strategies in China.

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Magnetic field-driven biochemical landscape of browning abatement in goat milk using spatial-omics uncovers - Rong Zhang; Wei Jia; Meng Zhang; Haiyan Xue; Huxuan Wang; Xixuan Wu (Food Chemistry, 2023)

Cadmium exposure during puberty damages testicular development and spermatogenesis via ferroptosis caused by intracellular iron overload and oxidative stress in mice - Yi Wang; Jie Wu; Mingming Zhang; Huijuan OuYang; Mengyuan Li; Didi Jia; Rong Wang; Weiyi Zhou; Hao Liu; Yuan Hu; Yuyou Yao; Yehao Liu; et al. (Environmental Pollution, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Effects of vegetation type differences induced by human disturbance on the nutrition strategy and gut microbiota of Siberian roe deer - Zi‐ao Yuan; Lin‐qiang Zhong; Hai‐rong Du; Jia‐nan Feng; Xin‐xin Liu; Hong‐yi Yuan; Jin‐hao Guo; Peng Liu; Ming‐hai Zhang (Molecular Ecology, 2023)
The Siberian roe deer ( Capreolus pygargus ) is a widely distributed ungulate in northeast China. Due to a series of human disturbance activities such as large‐scale forest cutting, deforestation and reclamation, road construction in the past, the appearance and internal structure of forest vegetation in the habitat of Siberian roe have changed significantly. At the same time, Siberian roe population had a series of ecological adaptation responses in the face of such habitat changes. Therefore, two typical vegetation types with differences were selected in the Muling Forest, China. We used nutritional ecology and microbial metagenomic analysis techniques to compare the nutritional selection strategy and the structure and functional characteristics of faecal microbiota of Siberian roe groups in two vegetation types. The results showed that the α diversity of dietary and gut microbes of deer in Natural Forest was higher than that in Plantation Forest. However, the gut microbes of the Plantation Forest group contained more unique enzymes in the functional pathways of carbon metabolism and biosynthesis of amino acids. This study suggests that habitat type is associated with plant community composition, and contributes to changes in the intake proportions of major macronutrients by altering the availability, quality, and composition of certain edible plants. Feeding behaviour may be an important regulatory factor of gut microbiota structure and function of deer. The metabolic function of gut microbiota to different nutrients may affect the microbial community structure. Therefore, our results suggest that the gut microbes of Siberian roe may have coevolved with their diets, and reflect the adaptability of deer populations to environmental changes (e.g., vegetation type). Our study provides new insights into how spatial heterogeneity affects nutrition and microecosystems by describing the interactions among the environment, diet, and symbiotic gut microbes in wild ungulates.

Bioaccumulation determines the toxicity of carbon dots to two marine dinoflagellates - Yue-Yue Liu; Jia-Meng Li; Rong Ji; Hongguo Zhang; Wei Zhang; Ai-Jun Miao (Chemosphere, 2023)

Evaluation of negative effect of Naphthenic acids (NAs) on physiological metabolism and polycyclic aromatic hydrocarbons adsorption of Phragmites australis - Hui Jia; Guang-xi Zhang; Yi-fan Wu; Wei-wei Dai; Quan-bin Xu; Shu Gan; Xiu-yun Ju; Zhao-zhong Feng; Rong-peng Li; Bo Yuan (Chemosphere, 2023)

Efficient inactivation of the contamination with pathogenic microorganisms by a combination of water spray and plasma-activated air - Li Guo; Pengyu Zhao; Yikang Jia; Tianhui Li; Lingling Huang; Zifeng Wang; Dingxin Liu; Zhanwu Hou; Yizhen Zhao; Lei Zhang; Hua Li; Yu Kong; et al. (Journal of Hazardous Materials, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Electrophilic components from Xiaoheiyao (rhizomes of Inula nervosa Wall.) alleviate the production of heterocyclic aromatic amines via creatinine inhibition - Xiang-Rong Cheng; Jia-Hui Ma; Issoufou Amadou; Wei Zhao; Yu-Yao Chen; Chen-Xi Zhang; Bin Guan (Food Chemistry, 2023)

Mechanism of natural antioxidants regulating advanced glycosylation end products of Maillard reaction - Wei Jia; Aiai Guo; Rong Zhang; Lin Shi (Food Chemistry, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

The Structure and Function of Glial Networks: Beyond the Neuronal Connections - Hai-Rong Peng; Yu-Kai Zhang; Jia-Wei Zhou (Neuroscience Bulletin, 2023)

Differences in lipid accumulation and mobilization in the hepatopancreas and ovary of female mud crab (Scylla paramamosain, Estampador, 1949) during ovarian development - Baojia Chen; Jia Zheng; Cuiying Chen; Kun Wu; Fan Lin; Lijun Ning; Hua Rong; Chuan Chen; Fei Xiao; Haotian Zhang; Xiaobo Wen (Aquaculture, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Associations of essential element serum concentrations with autism spectrum disorder - Jing Wu; Dongfang Wang; Lailai Yan; Meixiang Jia; Jishui Zhang; Songping Han; Jisheng Han; Jingyu Wang; Xi Chen; Rong Zhang (Environmental Science and Pollution Research, 2022)

Tetramethylpyrazine protects neural stem cells against sevoflurane-induced toxicity through Akt/GSK-3β pathway - Yan Feng; Kui Wang; Ning Wang; Pengyu Jia; Lei Zhang; Haozheng Yuan; Pan Lu; Yang Lu; Hong Zhang; Rong Li; Yan Zhang; Qianqian Li; et al. (Metabolic Brain Disease, 2022)

Hybrid brain model accurately predict human procrastination behavior - Zhiyi Chen; Rong Zhang; Jiawei Xie; Peiwei Liu; Chenyan Zhang; Jia Zhao; Justin Paul Laplante; Tingyong Feng (Cognitive Neurodynamics, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

Neiella holothuriorum sp. nov., isolated from the gut of a sea cucumber Apostichopus japonicus - Xin-Feng Bai; Xue-Lian Lv; Xue Liu; Ting-Ting Cui; Mian-Song Zhang; Ning Ding; Chang-Heng Liu; Ai-Rong Jia (Antonie van Leeuwenhoek, 2022)

Non-vernalization requirement in Chinese kale caused by loss of BoFLC and low expressions of its paralogs - Qiwei Tang; Hanhui Kuang; Changchun Yu; Guanghui An; Rong Tao; Weiyi Zhang; Yue Jia (Theoretical and Applied Genetics, 2022)
Key message We identified the loss of BoFLC gene as the cause of non-vernalization requirement in B. oleracea . Our developed codominant marker of BoFLC gene can be used for breeding program of B. oleracea crops . Abstract Many species of the Brassicaceae family, including some Brassica crops, require vernalization to avoid pre-winter flowering. Vernalization is an unfavorable trait for Chinese kale ( Brassica oleracea var. chinensis Lei ), a stem vegetable, and therefore it has been lost during its domestication/breeding process. To reveal the genetics of vernalization variation, we constructed an F 2 population through crossing a Chinese kale (a non-vernalization crop) with a kale (a vernalization crop). Using bulked segregant analysis (BSA) and RNA-seq, we identified one major quantitative trait locus (QTL) controlling vernalization and fine-mapped it to a region spanning 80 kb. Synteny analysis and PCR-based sequencing results revealed that compared to that of the kale parent, the candidate region of the Chinese kale parent lost a 9,325-bp fragment containing FLC homolog ( BoFLC ). In addition to the BoFLC gene, there are four other FLC homologs in the genome of B. oleracea , including Bo3g005470 , Bo3g024250 , Bo9g173370, and Bo9g173400 . The qPCR analysis showed that the BoFLC had the highest expression among the five members of the FLC family. Considering the low expression levels of the four paralogs of BoFLC , we speculate that its paralogs cannot compensate the function of the lost BoFLC, therefore the presence/absence (PA) polymorphism of BoFLC determines the vernalization variation. Based on the PA polymorphism of BoFLC , we designed a codominant marker for the vernalization trait, which can be used for breeding programs of B. oleracea crops.

The anticancer potential of the dietary polyphenol rutin: Current status, challenges, and perspectives - Arakkaveettil Kabeer Farha; Ren-You Gan; Hua-Bin Li; Ding-Tao Wu; Atanas G. Atanasov; Khalid Gul; Jia-Rong Zhang; Qiong-Qiong Yang; Harold Corke (Critical Reviews in Food Science and Nutrition, 2022)

Discovery of Genetic Biomarkers for Alzheimer’s Disease Using Adaptive Convolutional Neural Networks Ensemble and Genome-Wide Association Studies - An Zeng; Huabin Rong; Dan Pan; Longfei Jia; Yiqun Zhang; Fengyi Zhao; Shaoliang Peng (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Three-dimensional numerical simulation of geothermal field in space—wavenumber domain - Dai Shi-Kun; Jia Jin-Rong; Qiang Jian-Ke; Chen Qing-Rui; Ling Jia-Xuan; Zhang Ying (Applied Geophysics, 2021)

Lignans and phenylpropanoids from the liquid juice of phyllostachys edulis - De-Tao Wang; Ying-Ying Xue; Ying-Fang Zhang; Hang Xun; Qi-Rong Guo; Feng Tang; Jia Sun; Fei-Fei Qi (Natural Product Research, 2021)

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Antidepressant Effect of Paeoniflorin Is Through Inhibiting Pyroptosis CASP-11/GSDMD Pathway - Dan-Dan Tian; Min Wang; An Liu; Mei-Rong Gao; Chen Qiu; Wen Yu; Wen-Ju Wang; Kun Zhang; Le Yang; Yan-Yan Jia; Chang-Bin Yang; Yu-Mei Wu (Molecular Neurobiology, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

Toonapolyynes A–D, new polyynes from Toona ciliata - Rong Wang; Fu-Qiang Ni; Jun Sang; Yao Zhang; Jia-Luo Huang; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Protective effects of methane-rich saline on mice with allergic asthma by inhibiting inflammatory response, oxidative stress and apoptosis - Ning Zhang; Hong-tao Lu; Rong-jia Zhang; Xue-jun Sun (Journal of Zhejiang University-SCIENCE B, 2019)

Quadruplex PCR detection of three quarantine Phytophthora pathogens of berries - Fang Liao; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Doudou Zhang; Jia-Feng Luo; Guan-Rong Li (European Journal of Plant Pathology, 2019)

HL2 on chromosome 7D of wheat (Triticum aestivum L.) regulates both head length and spikelet number - Hongni Yao; Quan Xie; Shulin Xue; Jing Luo; Jikang Lu; Zhongxin Kong; Yongpan Wang; Wenling Zhai; Nan Lu; Rong Wei; Yang Yang; Yuzhou Han; et al. (Theoretical and Applied Genetics, 2019)

A study of the characteristics of energy flux and its relationship with the summer monsoon over alpine wetlands in the source region of the Yellow River - Dongyu Jia; Jun Wen; Yaoming Ma; Juan Zhou; Jinlei Chen; Rong Liu; Xin Wang; Tangtang Zhang; Xin Lai; ZuoLiang Wang (Meteorology and Atmospheric Physics, 2019)

Polyphenol Removal from Sugarcane Juice by Using Magnetic Chitosan Composite Microparticles - Xing-quan Liang; Song-lin Fan; Jia-xing Zhang; Xiao-rong Song (Sugar Tech, 2019)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

Association between serum somatostatin levels and glucose-lipid metabolism in the Jino ethnic minority and Han Chinese population - Shiyun Wang; Rong Zhang; Xuhong Hou; Fusong Jiang; Jie Wang; Zhen He; Feng Jiang; Cheng Hu; Weiping Jia (Science China Life Sciences, 2018)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

The warm season characteristics of the turbulence structure and transfer of turbulent kinetic energy over alpine wetlands at the source of the Yellow River - Dongyu Jia; Jun Wen; Yaoming Ma; Xin Wang; Tangtang Zhang; Rong Liu; Xin Lai (Meteorology and Atmospheric Physics, 2018)

Hydrological response of biological soil crusts to global warming: A ten‐year simulative study - Xin‐Rong Li; Rong‐Liang Jia; Zhi‐Shan Zhang; Peng Zhang; Rong Hui (Global Change Biology, 2018)
Biological soil crusts across the desert regions play a key role in regional ecological security and ecological health. They are vital biotic components of desert ecosystems that maintain soil stability, fix carbon and nitrogen, influence the establishment of vascular plants, and serve as habitats for a large number of arthropods and microorganisms, as well as influencing soil hydrological processes. Changes in temperature and precipitation are expected to influence the functioning of desert ecosystems by altering biotic components such as the species composition of biological soil crusts. However, it remains unclear how these important components will respond to the prolonged warming and reduced precipitation that is predicted to occur with climate change. To evaluate how the hydrological properties of these biological soil crusts respond to these alterations, we used open‐top chambers over a 10‐year period to simulate warming and reduced precipitation. Infiltration, dew entrapment, and evaporation were measured as surrogates of the hydrological functioning of biological soil crusts. It was found that the ongoing warming coupled with reduced precipitation will more strongly affect moss in crustal communities than lichens and cyanobacteria, which will lead to a direct alteration of the hydrological performance of biological soil crusts. Reductions in moss abundance, surface cover, and biomass resulted in a change in structure and function of crustal communities, decreased dew entrapment, and increased infiltration and evaporation of biological soil crusts in desert ecosystems, which further impacted on the desert soil water balance.

Regulation of myostatin expression is associated with growth and muscle development in commercial broiler and DMC muscle - Tengfei Dou; Zhengtian Li; Kun Wang; Lixian Liu; Hua Rong; Zhiqiang Xu; Ying Huang; Dahai Gu; Xiaobo Chen; Wenyuan Hu; Jiarong Zhang; Sumei Zhao; et al. (Molecular Biology Reports, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Triplex real-time PCR detection of three quarantine Phytophthora pathogens infecting Malus Miller - Fang Liao; Ying Zhang; Lin-Hui Zhu; Baohong Cao; Dajin Lv; Jia-Feng Luo; Guan-Rong Li (Journal of Plant Diseases and Protection, 2018)

Joint Interpretation of Geological, Magnetic, AMT, and ERT Data for Mineral Exploration in the Northeast of Inner Mongolia, China - Gang Zhang; Qing-Tian Lü; Gui-Bin Zhang; Ping-Rong Lin; Zheng-Yuan Jia; Kui Suo (Pure and Applied Geophysics, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Globular adiponectin inhibits leptin-stimulated esophageal adenocarcinoma cell proliferation via adiponectin receptor 2-mediated suppression of UHRF1 - Jun Wang; Yan Cheng; Xiaoran Yin; Jie Wu; Yumei Luo; Jing Wu; Jia Di; Dong Liu; Yahui Huang; Rong Zhang; Jun Zhang (Molecular and Cellular Biochemistry, 2017)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Accelerating Regulated Bioanalysis for Biotherapeutics: Case Examples Using a Microfluidic Ligand Binding Assay Platform - Rong Liu; Brian Hoffpauir; Shannon D Chilewski; Janice Gamberdella; Uma Kavita; Jia Duo; Carol Gleason; Yan Zhang; Renuka Pillutla; Binodh DeSilva; Lora Hamuro (The AAPS Journal, 2017)

Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Plasma Oxytocin and Arginine-Vasopressin Levels in Children with Autism Spectrum Disorder in China: Associations with Symptoms - Hong-Feng Zhang; Yu-Chuan Dai; Jing Wu; Mei-Xiang Jia; Ji-Shui Zhang; Xiao-Jing Shou; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2016)

Strawberry MOTHER OF FT AND TFL1 regulates seed germination and post-germination growth through integrating GA and ABA signaling in Arabidopsis - Yang Hu; Yu-Rong Gao; Wei Wei; Kai Zhang; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Identification of QTL for maize grain yield and kernel-related traits - CONG YANG; LEI ZHANG; AIMIN JIA; TINGZHAO RONG (Journal of Genetics, 2016)

Microbial community characteristics during simultaneous nitrification-denitrification process: effect of COD/TP ratio - Jian Zhang; Wenlin Jia; Rong Wang; Huu Hao Ngo; Wenshan Guo; Huijun Xie; Shuang Liang (Environmental Science and Pollution Research, 2016)

Genome-wide characterization and analysis of F-box protein-encoding genes in the Malus domestica genome - Hao-Ran Cui; Zheng-Rong Zhang; Wei lv; Jia-Ning Xu; Xiao-Yun Wang (Molecular Genetics and Genomics, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Effects on Pharmacokinetics of Propranolol and Other Factors in Rats After Acute Exposure to High Altitude at 4,010 m - Li Wenbin; Wang Rong; Xie Hua; Zhang Juanhong; Wu Xiaoyu; Jia Zhengping (Cell Biochemistry and Biophysics, 2015)

Rainfall and tillage impacts on soil erosion of sloping cropland with subtropical monsoon climate — A case study in hilly purple soil area, China - Jia-liang Tang; Xun-qiang Cheng; Bo Zhu; Mei-rong Gao; Tao Wang; Xi-feng Zhang; Pei Zhao; Xiang You (Journal of Mountain Science, 2015)

Heavy metal and organic contaminants in mangrove ecosystems of China: a review - Zai-Wang Zhang; Xiang-Rong Xu; Yu-Xin Sun; Shen Yu; Yong-Shan Chen; Jia-Xi Peng (Environmental Science and Pollution Research, 2014)

Studies on the analgesic activities of Jia-Yuan-Qing pill and its safety evaluation in mice - Ye Tian; Li-rong Teng; Jing-jing Song; Qing-fan Meng; Jia-hui Lu; Wei-wei Zhang; Kang Wei; Ning Wang; Di Wang; Le-sheng Teng (Protoplasma, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Association between melatonin receptor 1A (MTNR1A) gene single-nucleotide polymorphisms and the velvet antler yield of Sika deer - Fei-Fei Yang; Li-Jun Huo; Li-Guo Yang; Hasan Riaz; Li-Rong Xiong; Jian-Guo Chen; Shu-Jun Zhang; Jia-Jun Xiong (Molecular Biology Reports, 2014)

Characterization of eubacterial and archaeal community diversity in the pit mud of Chinese Luzhou-flavor liquor by nested PCR–DGGE - Xiao-Fei Ding; Chong-De Wu; Li-Qiang Zhang; Jia Zheng; Rong-Qing Zhou (World Journal of Microbiology and Biotechnology, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Determination of Concentration of Methotrexate Enantiomers in Intracellular and Extracellular Fluids of HepG2 Cells by Liquid Chromatography–Tandem Mass Spectrometry - Rong Wang; Lifang Guo; Hua Xie; Juanhong Zhang; Xiaoyun Li; Wenbing Li; Jianfeng Wang; Xiaoyu Wu; Zhengping Jia (Cell Biochemistry and Biophysics, 2013)

Neuroprotective effects of flavonoids extracted from licorice on kainate-induced seizure in mice through their antioxidant properties - Ling-hui Zeng; Hua-dan Zhang; Cai-ju Xu; Yu-jia Bian; Xue-jiao Xu; Qiang-min Xie; Rong-hua Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Effect of sand-stabilizing shrubs on soil respiration in a temperate desert - Zhi-Shan Zhang; Xin-Rong Li; Robert S. Nowak; Pan Wu; Yan-Hong Gao; Yang Zhao; Lei Huang; Yi-Gang Hu; Rong-Liang Jia (Plant and Soil, 2013)

Lack of association between SLCO1B1 polymorphism and the lipid-lowering effects of atorvastatin and simvastatin in Chinese individuals - Qiang Fu; Yan-Peng Li; Yuan Gao; Song-Hua Yang; Pei-Qi Lu; Min Jia; Li-Rong Zhang (European Journal of Clinical Pharmacology, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

Effects of breeds and dietary protein levels on the growth performance, energy expenditure and expression of avUCP mRNA in chickens - Qihua Li; Zhiqiang Xu; L. Liu; Hongxin Yu; Hua Rong; Linli Tao; Xi Zhang; Xiaobo Chen; Dahai Gu; Yueyuan Fan; Xiaoqin Li; Changrong Ge; et al. (Molecular Biology Reports, 2013)

Pharmacokinetics Study of Amoxycillin and Clavulanic acid (8:1)-A New Combination in Healthy Chinese Adult Male Volunteers Using the LC–MS/MS Method - Juanhong Zhang; Yinfu Wang; Hua Xie; Rong Wang; Zhengping Jia; Xiandong Men; Liting Xu; Qiang Zhang (Cell Biochemistry and Biophysics, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Determination of the geographical origin of Chinese teas based on stable carbon and nitrogen isotope ratios - Long Zhang; Jia-rong Pan; Cheng Zhu (Journal of Zhejiang University-SCIENCE B, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Polymorphism of CAG repeats in androgen receptor of carnivores - Qin Wang; Xiuyue Zhang; Xiaofang Wang; Bo Zeng; Xiaodong Jia; Rong Hou; Bisong Yue (Molecular Biology Reports, 2012)

Nitrification activity and putative ammonia-oxidizing archaea in acidic red soils - Rong Huang; Yucheng Wu; Jinbo Zhang; Wenhui Zhong; Zhongjun Jia; Zucong Cai (Journal of Soils and Sediments, 2012)

Synthesis of Benzimidazoles Containing Pyrazole Group and Quantum Chemistry Calculation of Their Spectroscopic Properties and Electronic Structure - Ren Tie-gang; Cheng Hong-bin; Zhang Jing-lai; Li Wei-jie; Guo Jia; Yang Li-rong (Journal of Fluorescence, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Mitochondrial Permeability Transition Induced by Different Concentrations of Zinc - Xiao-Rong Liu; Jia-Han Li; Yue Zhang; Yu-Shu Ge; Fang-Fang Tian; Jie Dai; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2011)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

Spectroscopic and Microscopic Studies on the Mechanisms of Mitochondrial Toxicity Induced by Different Concentrations of Cadmium - Yue Zhang; Jia-Han Li; Xiao-Rong Liu; Feng-Lei Jiang; Fang-Fang Tian; Yi Liu (The Journal of Membrane Biology, 2011)

Biophysical Studies on the Interactions of a Classic Mitochondrial Uncoupler with Bovine Serum Albumin by Spectroscopic, Isothermal Titration Calorimetric and Molecular Modeling Methods - Yue Zhang; Jia-Han Li; Yu-Shu Ge; Xiao-Rong Liu; Feng-Lei Jiang; Yi Liu (Journal of Fluorescence, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Identification and characterization of a novel ∆6-fatty acid desaturase gene from Rhizopus nigricans - He Lu; Jia-Na Li; You-Rong Chai; Xue-Kun Zhang (Molecular Biology Reports, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Detection of plasmid-mediated IMP-1 metallo-β-lactamase and quinolone resistance determinants in an ertapenem-resistant Enterobacter cloacae isolate - Li-rong Chen; Hong-wei Zhou; Jia-chang Cai; Rong Zhang; Gong-xiang Chen (Journal of Zhejiang University-SCIENCE B, 2009)

Molecular cytogenetic characterization of wheat–Secale africanum amphiploids and derived introgression lines with stripe rust resistance - Zu-Jun Yang; Guang-Rong Li; Ju-Qing Jia; Xue Zeng; Meng-Ping Lei; Zi-Xian Zeng; Tao Zhang; Zheng-Long Ren (Euphytica, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Distribution, biomass, and dynamics of roots in a revegetated stand of Caragana korshinskii in the Tengger Desert, northwestern China - Zhi-Shan Zhang; Xin-Rong Li; Li-Chao Liu; Rong-Liang Jia; Jing-Guang Zhang; Tao Wang (Journal of Plant Research, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Molecular cloning of Brassica napus TRANSPARENT TESTA 2 gene family encoding potential MYB regulatory proteins of proanthocyanidin biosynthesis - Yun-Liang Wei; Jia-Na Li; Jun Lu; Zhang-Lin Tang; Dong-Chun Pu; You-Rong Chai (Molecular Biology Reports, 2007)

Berbamine induces apoptosis in human hepatoma cell line SMMC7721 by loss in mitochondrial transmembrane potential and caspase activation - Guan-yu Wang; Jia-wei Zhang; Qing-hua Lü; Rong-zhen Xu; Qing-hua Dong (Journal of Zhejiang University-SCIENCE B, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Mutation induced by ethylmethanesulphonate (EMS), in vitro screening for salt tolerance and plant regeneration of sweet potato (Ipomoea batatas L.) - Yu-Shi Luan; Juan Zhang; Xiao-Rong Gao; Li-Jia An (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

Pharmacokinetics of three proton pump inhibitors in Chinese subjects in relation to the CYP2C19 genotype - Hai-Ling Qiao; Yu-Rong Hu; Xin Tian; Lin-Jing Jia; Na Gao; Li-Rong Zhang; Yu-Zhong Guo (European Journal of Clinical Pharmacology, 2006)

Measurement of 2H distribution in natural products by quantitative 2H NMR: An approach to understanding metabolism and enzyme mechanism? - Richard J. Robins; Isabelle Billault; Jia-Rong Duan; Sébastien Guiet; Sébastien Pionnier; Ben-Li Zhang (Phytochemistry Reviews, 2003)